Public debt sustainability in Africa: Building resilience and challenges ahead - Mthuli Ncube; Zuzana Brixiová (Institute for the Study of Labor (IZA), 2015)
The increased access of African countries to international capital markets has put public debt sustainability once again high on the continents policy agenda. Utilizing the "stabilizing primary balance" approach, we find that the primary balances exceeded those required to keep public debt at the 2007 level in about half of the countries studied. In several cases with high debt burdens, the balances were above those needed to reduce public debt-to-GDP to sustainable thresholds. In most countries the main driver of sustainability has been the interest rate - growth differential (IRGD), underscoring the importance of supporting growth and utilizing the borrowing space for growth-enhancing outlays. Fiscal policies will need to play a greater role in maintaining debt sustainability in the future, especially since the IRGDs are likely to narrow over the longer term. The recent developments such as the fall of the commodity prices and uneven global growth underscore the need for sound macroeconomic and risk management.
Keywords: H6; E6; O23; 330; public debt; sovereign bonds; interest-growth differential; primary balance; Africa